Birth Rate and Birth Weight of Crossbred Calves in Andaman and Nicobar Islands - Perumal, P.; De, A. K.; Bhattacharya, D.; Kundu, A.; Sunder, Jai; Ravi, S. K.; Bala, P. A.; Alyethodi, R. R.; Ahmed, S. K. Zamir (International Journal of Bio-resource and Stress Management, 2019)
Effect of month, season and year on calving pattern and birth weight of calves in crossbred dairy cows reared under semi-intensive organised farm in Andaman and Nicobar Islands, India was analysed. The birth rate and birth weight data of 207 calves born during 1999 to 2016 at Livestock Farm Complex, ICAR-Central Island Agricultural Research Institute (ICAR-CIARI), Andaman and Nicobar Islands, India was analysed. Calving rate (%) and birth weight of calves (kg) under different months (January to December), seasons (wet and dry seasons) and years (1999 to 2016) were calculated. Relative female ratio (RFR) and secondary sex ratio (SSR) were also calculated to assess the sex ratio of the calves in dairy farm. Result revealed highest birth rate in the months of April, August and May, intermediate in January, February, and October to December and lowest in March, June, July and September. Birth-rate (year-wise) showed a non-cyclical fluctuation throughout the period of data analysis. Birth weight was non-significantly (p=0.05) differed between sexes, among seasons, months and years. Birth weight was non-significantly (p=0.05) higher in male than in female and in wet than in dry season. Maximum calving was during wet season. In conclusion, sex ratio and birth weight were not differed among the months or among years or between seasons. However, wet season/months were found to be most conducive for breeding of crossbred cattle under semi-intensive system in Andaman and Nicobar Islands, India.